PENGARUH TEKANAN VAKUM TERHADAP KEMURNIAN OKSIGEN PADA PROSES VACUUM PRESSURE SWING ADSORPTION: - - Sugondo, Amelia; Sutrisno, Teng; Saputra , Richard M. Saputra (Jurnal Rekayasa Mesin, 2024)
Air pollution is an environmental problem that interferes with human health. This pollution is difficult to avoid due to the development of industry and transportation which are not fully environmentally friendly. Air pollution contributes 15-30% of health problems, especially breathing. One of the respiratory diseases is chronic obstructive pulmonary disease (COPD), the highest cause of death of the four other types of respiratory diseases. COPD sufferers need to get fresh air with a high oxygen content. The oxygen requirement can be produced by using cryogenic, adsorption and membrane technology. This study developed equipment for long-term oxygen therapy for COPD patients. Several adsorption methods have been developed, namely Vacuum Swing Adsorption (VSA), Pressure Swing Adsorption (PSA) and Vacuum Pressure Swing Adsorption (VPSA). VPSA was designed and used for this research because it can produce oxygen purity higher and more efficiently than others. This method utilizes vacuum pressure. VPSA was designed with 2 beds containing 13x zeolite added with activated alumina and 1 bed containing carbon molecular sieve (CMS). Experiments were carried out with a vacuum pressure setting of 0.35 bar, 0.5 bar and without vacuum to study the effect on oxygen purity, recovery process and productivity. From the experiments it was found that increasing the vacuum pressure can produce higher oxygen purity, but the opposite is true for recovery conditions from zeolite and oxygen productivity.